Patient–Provider Communication Barriers and Facilitators to HIV and STI Preventive Services for Adolescent MSM - Fisher, Celia B.; Fried, Adam L.; Macapagal, Kathryn; Mustanski, Brian (AIDS and behavior, 2018)
Adolescent males who have sex with males (AMSM) are at increased risk of contracting HIV/AIDS and other sexually transmitted infections (STIs). Healthcare providers are a critical source of HIV/STI prevention, yet little is known about AMSM patient–provider sexual health communications and services. To explore this issue, we surveyed a national sample of 198 AMSM 14–17 years. Four online psychometrically validated scales indicated over half the youth avoided communicating their sexual orientation and sexual health concerns to providers due to fear of heterosexist bias, concern their sexual health information would be disclosed to parents, and a general belief that sexual minority youth do not receive equitable treatment in health care settings. Youth who reported their physicians had initiated discussion about their sexual orientation were significantly more likely to have received HIV/STI preventive services and testing. Discussion includes the importance of medical training that meets the unique sexual health needs of AMSM.